Examining the relationship between purposeful heading in soccer and computerized neuropsychological test performance - Kamisnski, T. W.; Cousino, E. S.; Glutting, J. J. (Research Quarterly for Exercise and Sport, 2008)
The purpose of this study was to determine if a relationship exists between purposeful heading in soccer and neuropsychological test performance. Automated Neuropsychological Assessment Metrics throughput scores were derived on seven subset variables that measure a variety of neurocognitive abilities. Simple Spearman's rank correlations were calculated between headers per game (HPG) and the criterion variables. Interestingly, math processing speed (Spearman's rho = .160) and continuous performance test #2 (rho = .124) had small but significant correlations; both showed improvement in performance pre- to postseason. There were no significant correlations between HPG and the other five variables. This study found no detrimental relationship between the number of purposeful headers and the neurocognitive measures in this population.